2022
DOI: 10.3390/horticulturae8060491
|View full text |Cite
|
Sign up to set email alerts
|

SlSPS, a Sucrose Phosphate Synthase Gene, Mediates Plant Growth and Thermotolerance in Tomato

Abstract: Heat stress (HS) has been considered as a severe threat to crop yields in recent years. Sucrose, as a major product of photosynthesis, plays an important role in plant growth and stress response. Sucrose phosphate synthase (SPS) is a key rate-limiting enzyme in the sucrose synthesis pathway in plants. However, its molecular mechanism and signaling pathway remain unclear. In this study, we identified a novel SPS gene (SlSPS) in tomato and generated over-expression and knock-out of SlSPS gene transgenic tomato p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The results indicated that different nitrogen levels increased the fructose, glucose, sucrose, and sorbitol content of apple compared to the control at different development periods. The results obtained in this paper are similar to those in citrus [25], tomatoes [17], melon [33], and date palm [34].…”
Section: Effects Of Different Nitrogen Levels On Soluble Sugarsupporting
confidence: 85%
See 3 more Smart Citations
“…The results indicated that different nitrogen levels increased the fructose, glucose, sucrose, and sorbitol content of apple compared to the control at different development periods. The results obtained in this paper are similar to those in citrus [25], tomatoes [17], melon [33], and date palm [34].…”
Section: Effects Of Different Nitrogen Levels On Soluble Sugarsupporting
confidence: 85%
“…Genes-encoding SPS was first discovered in wheat [13]. Subsequently, SPS has been cloned from various plants, including rice, maize, sorghum [14], Arabidopsis [15], tobacco [16], tomato [17], sugarcane [18], and poplar [19]. These previous studies indicated that the activity of SPS played a positive regulatory role in sucrose accumulation, and that the total sugar is mainly in the form of sucrose in sorghum stalks [13,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentially, one sucrose-phosphate synthase was up-regulated only in S708 and the gene involve in the sucrose synthesis pathway in plants. 61 Interestingly, we found that the genes involved in the processes of trehalose synthesis were up-regulated only in T722, which encoding the trehalose-6-phosphate phosphatase (TPP) and trehalose-6-phosphate synthase (TPS), respectively. 62 Mollavali and Börnke 62 found that most of tomato of TPS/TPP genes were induced by temperature stress, suggesting that trehalose synthesis pathway may play important role in plants temperature stress adaptation.…”
Section: Discussionmentioning
confidence: 96%